2016
DOI: 10.1039/c6ra11966b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of lignin demethylated at atmospheric pressure and its application in fast curing biobased phenolic resins

Abstract: Agricultural crop-based lignin was utilized to modify phenol-formaldehyde (PF) resin to prepare fast curing biobased phenolic resins by copolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 48 publications
2
68
0
Order By: Relevance
“…For the demethylation, a procedure reported by Li et al was used and slightly modified [33]. The sample (1 g), 0.1 g of Na 2 SO 3 as the demethylating reagent and 6 g of 2.5 mol NaOH solution were introduced into a 15 mL rolled rim glass on an analytical balance and homogenized.…”
Section: Synthesis Of Demethylated Kraft Ligninmentioning
confidence: 99%
See 2 more Smart Citations
“…For the demethylation, a procedure reported by Li et al was used and slightly modified [33]. The sample (1 g), 0.1 g of Na 2 SO 3 as the demethylating reagent and 6 g of 2.5 mol NaOH solution were introduced into a 15 mL rolled rim glass on an analytical balance and homogenized.…”
Section: Synthesis Of Demethylated Kraft Ligninmentioning
confidence: 99%
“…So far, various procedures have been explored to incorporate more OH groups into the lignin structure including hydroxymethylation, phenolation, demethylation, oxidation and reduction [31]. These modifications have been studied primarily in conjunction with phenol-formaldehyde (PF) resins or PU research using lignin as a replacement for fossil-based phenols and polyols [32].In 2016, Li et al reported using demethylation to enhance the chemical reactivity at atmospheric pressure to produce fast curing phenolic resins [33]. Another possibility for lignin demethylation is an enzymatically catalyzed reaction using fungi (i.e., white and brown rot fungi) or bacteria (i.e., Pseudomonas, Sphingomonas).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 4,000–400 cm −1 infrared spectral region of BPF and PF resins before and after aging were shown in Fig. , and the structural changes during aging was ascertained by a semiquantitative analysis method . The peak at 1,600 cm −1 was assigned to the aromatic skeletal vibration, which was almost unchanged in each reaction during aging.…”
Section: Resultsmentioning
confidence: 99%
“…The rising price of petroleum together with the scarcity of fossil feedstock and promoting environment‐friendly products have encouraged renewable resources . Hence, considerable efforts have been made to replace phenol partially with cheaper materials or renewable resources, such as urea , lignin , and plant oil .…”
Section: Introductionmentioning
confidence: 99%